Language and Ideologies in Mission Statements of State and Private Universities in Ghana - Timothy Hottoh-Ahiaduvor; Richard Ayertey Lawer; Yvette Djabakie Asamoah; Jemima Sam (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2026)
This study examines how state and private universities in Ghana construct institutional identities and ideological orientations through their mission statements. Drawing on Fairclough’s Critical Discourse Analysis (CDA) framework, the study analyses 63 mission statements to uncover the ideological categories encoded in these texts and the linguistic resources through which they are realized. The findings reveal thirty-two ideological orientations, with educational, developmental, professional, leadership, and national ideologies most frequently foregrounded. Linguistically, ideologies are naturalized through declarative sentence structures, non-finite clauses, nominalization, evaluative adjectives, and strategic representations of social actors. A comparative analysis shows that state universities predominantly align with national development, scientific advancement, and public service discourses, whereas private universities, especially faith-based ones, mobilize religious, entrepreneurial, global, and moral ideologies to differentiate their institutional identities. These patterns demonstrate that mission statements operate as ideological technologies that mediate institutional legitimacy, respond to socio-political pressures, and position universities within both local and global educational markets. The study contributes to Critical Discourse Studies by illuminating how higher education institutions in the Global South recontextualize globally circulating discourses within culturally and politically specific contexts. It also offers insights into how language functions as a strategic tool in institutional branding, policy alignment, and identity construction.